Comparison the effect of Phenobarbital and sodium valproate on seizure control in children - Khajeh, Ali; Yaghoubinia, Fariba; Yaghoubi, Saeedeh; Fayyazi, Afshin; Miri-Aliabad, Ghasem (Iranian Journal of Child Neurology, 2018)
Objectives: Acute prolonged seizure is the most common neurological emergency in children. This research was conducted to compare the effect of intravenous Phenobarbital and sodium valproate in control of seizure in children who were referred to emergency ward in 2013. Materials & Methods: In this randomized clinical trial, 80 children with prolonged seizure and with no response to one dose of diazepam (0.2 mg/kg) during the five minutes were selected. Children were randomly allocated into two groups, intervention and control through permutation blocks. In intervention group, intravenous sodium valproate (20mg/kg) and in control group, intravenous Phenobarbital (20 mg/kg) was prescribed. Data such as age, gender, history of previous seizure, seizure type and recovery time after receiving drug was recorded in the form. Data analysis was done through descriptive statistics, Chi-square and Independent T- Test. Results: Two groups were the same in terms of age and gender and have no statistically significant difference, but they were different in terms of seizure type (p=0.002). In valproate group, 18 patients (45 percent) and in Phenobarbital group, 32 patients (80 percent) have positive response to the treatment and the chi-square test showed the significant difference (p=0.001). The mean of response time to drug in intervention group was 6.17±2.99 and in control group was 4.71±2.38 minutes, but this difference was not statistically significant. Conclusion: Results of current study showed that the sodium valproate in comparison with Phenobarbital isn’t a suitable and effective drug for controlling of seizure in children